Assessment of Apically Extruded Debris after Using Different Endodontic Instrumentation systems. - Saif Nadhim Hassoon (University of Mosul, College of Dentistry, 2022)
Aims: Assess the quantity of apical extruded debris after instrumentation with ProTaper universal files, K3 files, and Wave One reciprocating file. Materials and Methods: Thirty lower premolars were used in this study. Teeth were randomly divided into 3 groups each one contained 10 samples as follow: Group1- Teeth were prepared with ProTaper universal files. Group2- Teeth were prepared with K3 files. Group3- Teeth were prepared with Wave One file. Debris that was apically extruded during canals preparation was collected in the centrifuge tubes, which previously were weighed. Centrifuge tubes were put for 5 days in the incubator with temperature of 70 °C to allow evaporation of moisture. After that centrifuge tubes that contained debris were weighed, and quantity of extruded debris was determined via subtraction the initial weight of centrifuge tube from the final weight of same tube, then collected data was analyzed statistically. Results: Statistical analysis revealed that, ProTaper group showed highest amount of apical extruded debris followed by Wave One group and, K3 group showed least amount of apical extruded debris. The difference between ProTaper group and Wave One group was not significant, but both of them had significant difference with K3 group. Conclusions: Within the limits of the current study, preparation of root canals with K3 files is better than other groups in terms of less extrusion of apical debris.